The Role Of Syrian Women In Roman Society - معلا, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Throughout history and ,the role of the woman has changed and was different and sometimes contradictory, It fluctuated from being considered an ineffective woman to being considered the lady and the ruler in the fate of society. And this is what we are going to consider in the following research, showing her role in the different aspects of life from political to social and religious life. And the woman could lead the Roman Impire and control it politically, and tried to achieve peace and stability in it, like Empress Julia Domna and Queen Zenobia. The Syrian woman participated in most of the empire's religious rituals, whether as a worshiper or priestess. Thus, the Syrian woman was able to immortalize her name through her contribution to building a civilization that testifies to her works throughout the ages.